A New Approach to Evaluate the Bactericidal Activity of Different Antiseptic Ophthalmic Preparations Used as Surgical Prophylaxis - Sara Caldrer; Niccolò Deotto; Marco G. Prato; Natasha Gianesini; Milena Bernardi; Pierantonio Orza; Federico G. Gobbi; Grazia Pertile; Chiara Piubelli (Antibiotics)
Background: A survey conducted by the European Observatory on Cataract Surgery showed high heterogeneity in the use of antiseptics both preoperatively and in the operating room, highlighting the absence of a global consensus regarding ocular infection prophylaxis in cataract surgery. Methods: The antibacterial activity of seven antiseptic ophthalmic formulations (AOFs) registered as medical devices and the two most common disinfectants were evaluated in vitro against five bacterial species. The viability of bacterial strains after exposure to the antiseptic was evaluated with different techniques: the in vitro Minimum Inhibitory Concentration and the subsequent Minimum Bactericidal Concentration, performed on liquid and solid culture medium. Furthermore, a real-time assessment of bacterial viability was conducted using double staining for live/dead bacterial cells by fluorimetric assay. This evaluation was performed on both the time-killing curve and the tear dilution effect test. Results: We observed a high variability across the different AOFs in terms of inhibitory/bactericidal concentration and timing on Gram-positive and Gram-negative bacterial classes. The results indicated that among the tested AOFs, Visuprime, Iodim, and Oftasteril were the most rapid and effective for ocular surface disinfection against the tested bacterial species. Conclusions: The obtained results can support the clinician’s choice of the most suitable AOF for the prevention and treatment of ophthalmic infections associated with surgery.